Acute duodenal diverticulitis with contained perforation causing biliary obstruction and ascending cholangitis: a case report - Keng, Cambo; Goai, Xin Yi; Pretorius, Casper F. (International Surgery Journal, 2026)
Periampullary duodenal diverticula (PAD) are common in older adults but rarely cause biliary obstruction and cholangitis. Distinguishing diverticulitis with contained perforation from other periampullary pathology can be challenging, and endoscopic visualisation may be limited by scope choice. An 83-year-old woman presented with two weeks of right upper-quadrant pain, associated with fever, jaundice and cholestatic derangement. CT and MRCP showed periampullary diverticulitis with contained perforation, causing common bile duct (CBD) obstruction; several small non‑obstructive CBD stones were also present. She met accepted criteria for definite acute cholangitis. In view of suspected diverticular perforation and anticipated technical challenges with endoscopic retrograde cholangiopancreatography (ERCP), she was managed conservatively with intravenous antibiotics and supportive care, with clinical and biochemical resolution. Follow-up CT intravenous cholangiogram showed normal calibre ducts and no filling defects. Forward-viewing gastroscopy later did not visualise diverticulum. PAD can present with diverticulitis and peridiverticular collection causing biliary obstruction and cholangitis, even when small non‑occlusive CBD stones coexist. Conservative management may be effective in selected stable patients when ERCP carries high risk and side‑viewing duodenoscopy should be considered when endoscopic visualisation is required.